DNA nanomapping using CRISPR-Cas9 as a programmable nanoparticle. Issue 1 (December 2017) - Mikheikin, Andrey; Olsen, Anita; Leslie, Kevin; Russell-Pavier, Freddie; Yacoot, Andrew; Picco, Loren; Payton, Oliver; Toor, Amir; Chesney, Alden; Gimzewski, James; Mishra, Bud; Reed, Jason
Abstract Progress in whole-genome sequencing using short-read (e.g., <150 bp), next-generation sequencing technologies has reinvigorated interest in high-resolution physical mapping to fill technical gaps that are not well addressed by sequencing. Here, we report two technical advances in DNA nanotechnology and single-molecule genomics: (1) we describe a labeling technique (CRISPR-Cas9 nanoparticles) for high-speed AFM-based physical mapping of DNA and (2) the first successful demonstration of using DVD optics to image DNA molecules with high-speed AFM. As a proof of principle, we used this new "nanomapping" method to detect and map precisely BCL2–IGH translocations present in lymph node biopsies of follicular lymphoma patents. This HS-AFM "nanomapping" technique can be complementary to both sequencing and other physical mapping approaches. Physical mapping of DNA can be used to detect structural variants and for whole-genome haplotype assembly. Here, the authors use CRISPR-Cas9 and high-speed atomic force microscopy to 'nanomap' single molecules of DNA.